Firearm restrictions in domestic violence protection orders: Implementation, vetting, compliance, and enforcement - Ellyson, Alice M. (Criminology & public policy, 2024)
Research Summary We quantified the implementation of WA state's domestic violence (DV)-related firearm prohibitions (RCW9.41.800) by the courts and the Regional Domestic Violence Firearms Enforcement Unit (RDVFEU), a regional approach to compliance promotion. We measured implementation, vetting, compliance, and enforcement of firearm prohibitions before (2014-2016) and after (2018-2020) the RDVFEU was implemented using a 55% random sample of granted domestic violence protection orders (DVPOs) in King County, WA (n = 3543). We evaluated differences in judicial orders to surrender firearms and other dangerous weapons (OTSWs), respondent documented compliance, and respondent weapon and/or firearm relinquishment before and after implementation. Compared to DVPOs granted prior to RDVFEU implementation, granted DVPOs after RDVFEU implementation were at least 4.5 times more likely to include an OTSW. RDVFEU implementation was also associated with at least 3.4 times the odds of respondent documented compliance and at least 3.3 times the odds of respondent relinquishment of at least one firearm and/or other dangerous weapon. These findings demonstrate RDVFEU implementation was associated with benefits at each stage of the protection order process with improvements in both judicial enforcement and respondent compliance. Overall, RDVFEU implementation was associated with improvements in granted orders to surrender weapons, respondent compliance, and relinquishment. Policy Implications DV-related firearm prohibitions can be supported by interdisciplinary teams within the legal system to promote respondent compliance and enhance safety planning for DV victim-survivors.